2018
DOI: 10.1016/j.radi.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of focused training on abnormality detection and provision of accurate preliminary clinical evaluation in newly qualified radiographers

Abstract: An 8-week training program had a positive impact on participants' ability to localise and accurately describe fractures. Implementation of abnormality detection training should be considered during preceptorship periods. Due to the small sample size, it is inappropriate to suggest these findings are representative of all graduate radiographers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…A future study may benefit from a pre and post additional abdominal radiograph interpretation education arm to the study. Studies focussing on musculoskeletal PCE have demonstrated the value of the integration of education with image interpretation schemes (23)(24)(25)(26). Each study shared a common theme that education can positively influence the image interpretation skill of the participant.…”
Section: Discussionmentioning
confidence: 99%
“…A future study may benefit from a pre and post additional abdominal radiograph interpretation education arm to the study. Studies focussing on musculoskeletal PCE have demonstrated the value of the integration of education with image interpretation schemes (23)(24)(25)(26). Each study shared a common theme that education can positively influence the image interpretation skill of the participant.…”
Section: Discussionmentioning
confidence: 99%
“…The participant results in this study were encouraging when compared to published studies assessing equivalent radiographic examinations 9,11,12,16,17, and applying similar scoring systems. 13,16,17 Radiographer image interpretation has been demonstrated extensively since the early work of Berman et al 49 and the systematic review by Brealey et al 89 through to the work of Piper and Paterson 16 and Coleman and Piper 17 addressing a multidisciplinary approach and in recent studies of PCE ability of radiographers in the UK, 8 South Africa 9 and Australia. 11,59,81,85 The literature review found a disposition towards qualitative research from the nursing profession discussing the role of requesting and triage of radiographic imaging in the acute setting from the UK [90][91][92][93] and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies [8][9][10][11][12] have shown the potential for radiographers to produce PCEs, with limited up to date literature demonstrating the image interpretation ability of other healthcare professionals [13][14][15][16][17][18][19][20][21] involved with the treatment and management of patients requiring radiographic imaging for trauma. The College of Paramedics 21 definition of the role of an advanced paramedic practitioner, in line with the Royal College of Emergency Medicine ACP pathway 22 for managing patients through accident and emergency (A&E) and urgent care pathways, includes requesting radiographic examinations and image interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…This approach provides an opportunity for participants to improve on their written commenting skills when interpreting radiographic images and conveying significant findings. The literature reveals a wide variation in normal to abnormal prevalence when compiling image test cases . In our study, we have used a ratio that is commonly encountered in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…A Queensland state ministerial taskforce argued that improvements to patient‐centred care, as well as service effectiveness and efficiency could be achieved by implementation of a full scope of practice for Allied Health professionals. Numerous studies have reported that tailored training in pattern recognition could improve radiographer's ability to identify fractures and dislocations and provide descriptive comments . Radiographers have an ethical and professional responsibility to the Australian public to provide an opinion on images produced using their knowledge and experience as expected by the MRPBA's professional capabilities document .…”
Section: Introductionmentioning
confidence: 99%